Crystal growth, structure and characterization of diglycine zinc dipicrate: Centrosymmetric crystal exhibiting second harmonic generation efficiency. (13th October 2017) - Sivaraman, S.; Balakrishnan, C.; Prasad, A. Aditya; Sokalingam, R. M.; Meenakshisundaram, S. P.; Markkandan, R.
GRAPHICAL ABSTRACT: ABSTRACT: Single crystals of diglycine zinc dipicrate (DZD) were grown by the slow evaporation solution growth technique from ethanol at room temperature. The structure is elucidated by single crystal XRD analysis and it belongs to the triclinic system with centrosymmetric space group Pī . The crystallinity of the material was confirmed by powder X-ray diffraction analysis. The functional groups present in the molecule are identified by FT-IR analysis and the band gap energy is estimated using diffuse reflectance data by the application of Kubelka–Munk algorithm. Investigation of the intermolecular interactions and crystal packing via Hirshfeld surface analysis, based on single-crystal XRD, reveals the close contacts associated with molecular interactions. Fingerprint plots of the Hirshfeld surfaces were used to locate and analyze the percentage of hydrogen-bonding interactions.The data are analysed by combined results of single crystal XRD and electronic structure calculations. Theoretical calculations done by density functional theory(DFT) gives an idea about structure-function relationship. The second harmonic generation efficiency (SHG) is estimated using the Kurtz and Perry technique and it reveals second order nonlinearity. The observation of a centrosymmetric crystal exbiting NLO character is rationalized.